The patient voice: a survey of worries and anxieties during health system transition in HIV services in Vietnam - Shoko Matsumoto (BMC International Health and Human Rights, 2020)
Abstract Background Vietnam is shifting toward integrating HIV services into the public health system using social health insurance (SHI), and the HIV service delivery system is becoming decentralized. The study aim was to investigate current SHI coverage and patients’ perspectives on this transition. Methods A survey of 1348 HIV-positive patients on antiretroviral therapy (aged ≥18 years) was conducted at an HIV outpatient clinic at a central-level hospital in Hanoi, Vietnam, in October and November 2018. Insurance coverage, reasons for not having a SHI card, perceived concerns about receiving HIV services in SHI-registered local health facilities, and willingness to continue regularly visiting the current hospital were self-reported. Logistic regression analyses were performed to analyze factors associated with not having a SHI card and having concerns about receiving HIV services in SHI-registered hospitals/clinics. Results SHI coverage was 78.0%. The most frequently reported reason for not having a SHI card was that obtaining one was burdensome, followed by lack of information on how to obtain a card, and financial problems. Most patients (86.6%) had concerns about receiving HIV services at SHI-registered local health facilities, and disclosure of HIV status to neighbors and low quality of HIV services were the main concerns reported. Participants aged < 40 years old and unmarried were more likely to report lack of SHI cards, and women and those aged ≥40 years were more likely to have concerns. However, 91.4% of patients showed willingness to continue regular visits to the current hospital. Conclusions Although SHI coverage has been rapidly improving among HIV patients, most participants had concerns about the current system transition in Vietnam. In response to their voiced concerns, strengthening the link between higher-level and lower-level facilities may help to ensure good quality HIV services at all levels while mitigating patients’ worries and anxieties.